(-z)(-4z/-z-6)-1

Simple and best practice solution for (-z)(-4z/-z-6)-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-z)(-4z/-z-6)-1 equation:


D( z )

-z = 0

-z = 0

z = 0

z in (-oo:0) U (0:+oo)

-z*((-4*z)/(-z)-6)-1 = 0

-2*(-z)-1 = 0

-2*(-z)-1 = 0

2*z-1 = 0

2*z-1 = 0

2*z-1 = 0 // + 1

2*z = 1 // : 2

z = 1/2

z = 1/2

See similar equations:

| -5/8x-2=-7 | | 4(x+1)+19= | | 3y-5+y+25=5y+20-3y | | -5/8x-2 | | X^2+8x-20=64 | | 2x^2+6x-36= | | 2x^2+3xy-5y^2-8x-13y+6=0 | | (11x^3)-(25x^2)+(3x)=14 | | 3-5x=12+7X | | 2+5n=6n+2 | | 9t+21=2 | | 9x^2+18x-72= | | 4x+4=-2x+8 | | 12x^3-24x^2+3x+34=x^2-x^3+48 | | f(x)=x^2+6x+13 | | 6m^2+54=0 | | 90+(2*x-2)+(x+5)=180 | | 5x+1.50x=15.50 | | x^2+y^2+16x+18y+141=0 | | 3.16(x+4.63)=419(x-7.24) | | 7.3+1x= | | -4t^2-24t+13= | | 1.5x+7=4 | | 9n-8=6n+16 | | -14-2p=-6p-2+7p | | 33y=-2x+b | | (4/5)+(1/6)=1/x | | -0.8x=-64 | | 194.5/200= | | 7x-3=9x-15 | | x^2-35x-275=0 | | 12c+4=1 |

Equations solver categories